2016
DOI: 10.1002/advs.201600097
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Power Density of Microbial Fuel Cells with 3D Nitrogen‐Doped Graphene Aerogel Electrode

Abstract: A 3D nitrogen‐doped graphene aerogel (N‐GA) as an anode material for microbial fuel cells (MFCs) is reported. Electron microscopy images reveal that the N‐GA possesses hierarchical porous structure that allows efficient diffusion of both bacterial cells and electron mediators in the interior space of 3D electrode, and thus, the colonization of bacterial communities. Electrochemical impedance spectroscopic measurements further show that nitrogen doping considerably reduces the charge transfer resistance and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 43 publications
0
51
0
Order By: Relevance
“…Furthermore, it has been reported that charge transfer resistance of MFC is closely related to the efficiency of extracellular electron transport. [1c] The smaller the charge transfer resistance represents the higher the power delivering efficiency that is critical to MFC . Notably, the charge transfer resistances of the bacteria‐CNT composite electrodes [bacteria‐CNT‐1: 1.65 Ω cm −2 (20.72 Ω); bacteria‐CNT‐2: 1.44 Ω cm −2 (18.18 Ω)] are similar and considerably lower than the value obtained from the bacteria‐colonized‐CNT anode [2.65 Ω cm −2 (33.32 Ω)], and significantly lower than the values reported for carbon cloth anodes (>100 Ω cm −2 ) .…”
Section: Performances Comparison Between This Work and Reported Mfc Dmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, it has been reported that charge transfer resistance of MFC is closely related to the efficiency of extracellular electron transport. [1c] The smaller the charge transfer resistance represents the higher the power delivering efficiency that is critical to MFC . Notably, the charge transfer resistances of the bacteria‐CNT composite electrodes [bacteria‐CNT‐1: 1.65 Ω cm −2 (20.72 Ω); bacteria‐CNT‐2: 1.44 Ω cm −2 (18.18 Ω)] are similar and considerably lower than the value obtained from the bacteria‐colonized‐CNT anode [2.65 Ω cm −2 (33.32 Ω)], and significantly lower than the values reported for carbon cloth anodes (>100 Ω cm −2 ) .…”
Section: Performances Comparison Between This Work and Reported Mfc Dmentioning
confidence: 90%
“…It is anticipated that the power density of an MFC can be enhanced by increasing the number of electrogenic bacteria colonized on the anode, when the bio‐oxidation reaction is not limited by mass transfer (the diffusion of redox species) or charge transport (both direct and indirect extracellular electron transport) . In the past decade, a variety of new anode structures, such as carbon cloth, carbon nanotube (CNT)‐textile, macroporous reduced graphene oxide‐nickel (rGO‐Ni), 3D nitrogen‐doped graphene aerogel, etc. have been developed with a goal of increasing the electrode surface area for bacteria colonization.…”
Section: Performances Comparison Between This Work and Reported Mfc Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, N-doped graphene aerogel was used as an electrode in Li-ion supercapacitor and got a maximum energy density of 70 Wh/Kg with the power density of 200 Wh/Kg with good cycling stability [111]. N-doped graphene aerogel was also used as an anode material for microbial fuel cell and attained a power density of 225 W/m 3 with a high open circuit potential of 0.69 V [112].…”
Section: Graphene Aerogelsmentioning
confidence: 99%
“…Therefore, to make MFCs a competitive renewable technology, a lot of research focuses on the impact of the bioreactor structure, the used materials for the electrodes and the microbial community on the volumetric power density [2]. Recent MFCs achieve volumetric power densities of 225W m −3 , although on a small scale (25ml) and in a wellcontrolled lab environment [3].…”
Section: Introductionmentioning
confidence: 99%